Preparation‐related structural diversity and medical potential in the treatment of diabetes mellitus with ginseng pectins. Issue 1 (1st August 2017) - Chen, Qilei; Zhu, Lin; Tang, Yina; Zhao, Zhongzhen; Yi, Tao; Chen, Hubiao
Abstract: Pectins isolated from Panax ginseng C.A. Meyer are potential therapeutic agents for the treatment of diabetes mellitus, a global health challenge. Soil‐to‐bench procedures of ginseng pectin preparation significantly affect the polysaccharide structures. Various forms of ginseng pectins rich in homogalacturonan, rhamnogalacturonan‐I, rhamnogalacturonan‐II, and arabinogalactan have demonstrated independent or collaborative effects on hyperglycemia, oxidative stress, immunological dysfunction, and neoplasms. Monosaccharide compositions, peptide contents, degrees of esterification and methylation, and inter‐ and intramolecular linkages all influence pectin bioactivity. Understanding the preparation–structure and structure–function relationships of ginseng pectins can lead to safer and more pertinent treatment of diabetes with efficacy‐oriented modifications of the pectins. To reach this goal, standardization of preparation procedures, understanding of intricate structures, and exploration of complex interactions with receptors are crucial steps to take full advantage of the medical potential of ginseng pectins.